2002
DOI: 10.1128/iai.70.5.2336-2343.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Receptor Binding Specificity ofEscherichia coliK88 (F4) Fimbrial Adhesin Variants Using Porcine Serum Transferrin and Glycosphingolipids as Model Receptors

Abstract: Diarrheal disease caused by enterotoxigenic Escherichia coli expressing the K88 (F4) fimbrial adhesin (K88 ETEC) is a significant source of mortality and morbidity among newborn and weaned piglets. K88 fimbrial adhesins are filamentous surface appendages whose lectin (carbohydrate-binding) activity allows K88 ETEC to attach to specific glycoconjugates (receptors) on porcine intestinal epithelial cells. There are three variants of K88 adhesin (K88ab, K88ac, and K88ad), which possess different, yet related, carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 55 publications
2
47
1
Order By: Relevance
“…Furthermore, Payne et al [47] and Grange et al [5] determined that ␤-linked galactose is an important component in the recognition of intestinal mucus K88 receptors. K88 adhesin also interacts with lactosylated (Gal ␤ 1-4 GlcNAc) N-oligosaccharides present in serum and intestinal glycoproteins [29,48,49].…”
Section: E Coli K88 Adhesion Assaysmentioning
confidence: 99%
“…Furthermore, Payne et al [47] and Grange et al [5] determined that ␤-linked galactose is an important component in the recognition of intestinal mucus K88 receptors. K88 adhesin also interacts with lactosylated (Gal ␤ 1-4 GlcNAc) N-oligosaccharides present in serum and intestinal glycoproteins [29,48,49].…”
Section: E Coli K88 Adhesion Assaysmentioning
confidence: 99%
“…F4 fimbriae consist of the major adhesive subunit FaeG and the minor subunits FaeF, FaeH, FaeC and FaeI ( Van den Broeck et al 2000). The three variants of F4 fimbriae (ab, ac and ad) vary in FaeG sequence, and each shows a related but distinct binding profile to the glycoconjugate receptors on enterocytes (Grange 2002). After colonization, ETEC produce heat-labile enterotoxin (LT), heat-stable enterotoxin a and b (STa and STb) in different combinations (Fairbrother et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The important role for galactose and/or N-acetyl galactosamine residue in the F4 receptor structure was highlighted in different studies; most often these residues were present at the non-reducing end in ␤-linkage (24, 28, 30 -36). In other studies, the interaction of all F4 variants with different glycosphingolipids was demonstrated, such as lactosylceramide, gangliotriaosylceramide, gangliotetraosylceramide, globotriaosylceramide, lactotetraosylceramide, and lactotetraosylceramide (24,30,32,37). A more recent study investigated the glycosphingolipid recognition by the different F4 variants and found that the F4 ab and F4 ac variants showed more similarities in their glycosphingolipid recognition patterns when compared with the F4 ad variant (30).…”
mentioning
confidence: 86%